Factors Affecting Online Purchase Intention of Prospects: A Study in Nepalese Context - Rai, Arjun; Rai, Chandra Kumar (Dristikon: A Multidisciplinary Journal, 2022)
Various factors influence potential buyers' purchase intention from stores. Attitude towards online shopping, perceived customer service, quality, and price fairness may also determine the prospects' intention to buy or not. Amid Covid-19, many traditional stores adopted digital platforms to reach and serve customers. In this context, this study aimed to examine how the attitude towards online shopping, prospects' perception of customer service of online stores, quality perception, and price fairness perception affect purchase intention. This study used the Ordinary Least Square model to examine the effect of independent variables on the dependent variable. 3 presents the Correlation between the variables attitude, perceived customer service, quality, price fairness, and purchase intention of the respondents. The correlation test revealed significant positive correlations between the stated variables. The study employed a survey method to collect data from 425 respondents, using a structured-self administered questionnaire. The collected data were coded, entered, and analyzed in Statistical Package for Social Science (25). The result of the study indicated a significant positive impact of attitude, perceived customer service, quality perception, and price fairness perception on purchase intention. The contribution of this study highlights the positive impact of the stated variables on the purchase intention of the prospects in the Nepalese social context. This information may be helpful for online stores to improve their marketing performance.